Defect tolerance, anharmonicity, and organic-inorganic coupling in hybrid organic-inorganic semiconductors - Maughan, Annalise E., author; Neilson, James R., advisor; Prieto, Amy L., committee member; Reynolds, Melissa M., committee member; Sites, James R., committee member (Colorado State University. Libraries, 2018)
Implementing and improving sustainable energy technologies is predicated upon the discovery and design of new semiconducting materials. Perovskite halides represent a paradigm shift in solar photovoltaic technologies, as devices utilizing perovskites as the active semiconductor can achieve power conversion efficiencies rivaling those of commercial solar cells after less than a decade of dedicated research. In contrast to conventional semiconductors, perovskites are unique in that they exhibit excellent photovoltaic performance despite the presence of significant materials disorder. This disorder manifests as (1) a large concentration of crystallographic defects introduced by low-temperature processing, and (2) as dynamic disorder due to the deformable metal-halide framework and the presence of dynamic organic species within the crystalline voids. Vacancy ordered double perovskites of the general formula A2BX6 are a defect-ordered variant of the archetypal perovskite structure comprised of isolated [BX6] units bridged by cationic species at the A-site. The presence of ordered vacancies and relatively decoupled octahedral units presents an ideal system to investigate defects and lattice dynamics as they pertain to optical and electronic properties of perovskite halide semiconductors. This work aims to illuminate the fundamental structure-dynamics-property relationships in vacancy-ordered double perovskite and hybrid organic-inorganic semiconductors through a combination of advanced structural characterization, optical and electrical measurements, and insight from computation. We begin with a study of the Cs2Sn1-xTexI6 series of vacancy-ordered double perovskites to inform the chemical and bonding characteristics that impact defect chemistry in vacancy-ordered double perovskites. While the electronic properties of Cs2SnI6 are tolerant to the presence of crystallographic defects, introducing tellurium at the B-site yields an electronic structure that renders Cs2TeI6 defect-intolerant, indicating the importance of the B-site chemistry in dictating the optoelectronic properties in these materials. Next, we elucidate the interplay of the A-site cation with the octahedral framework and the subsequent influence upon lattice dynamics and optoelectronic properties of several tin-iodide based vacancy-ordered double perovskites. The coordination and bonding preferences of the A-site drive the structural and dynamic behavior of the surrounding octahedra and in turn dictate charge transport. A-site cations that are too small produce structures with cooperative octahedral tilting, while organic-inorganic coupling via hydrogen bonding yields soft, anharmonic lattice dynamics characterized by random octahedral rotations. Both regimes yield stronger electron-phonon coupling interactions that inhibit charge transport relative to undistorted analogs. The final study presented here details the discovery of two hybrid organic-inorganic semiconductors containing the organic tropylium cation within metal iodide frameworks. In C7H7PbI3, the tropylium electronic states couple to those of the lead iodide framework through organic-inorganic charge transfer. Electronic coupling between the organic and inorganic sublattices within a singular material provides an avenue to elicit unique optical and electronic properties unavailable to either components individually. The above work is then placed in context of other recent studies of vacancy-ordered double perovskite semiconductors, and a set of design principles are constructed. Future avenues of research are proposed. These structure-dynamics-property relationships represent an important step towards rational design of vacancy-ordered double perovskite semiconductors for potential optoelectronic applications.
Keywords: perovskite; disorder; semiconductors